2023
DOI: 10.1002/nbm.4910
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical correlations in short echo time proton magnetic resonance spectroscopy

Abstract: Neurochemical concentrations determined by magnetic resonance spectroscopy (MRS) have been treated as statistically independent measurements in various clinical MRS studies. However, spectral overlap, independent of any biological effects, could lead to significant correlations between neurochemical concentrations extracted from spectral fitting of MRS data, confounding determination of correlations of biological origin. Short echo time (TE) proton MRS spectra are very crowded because of the comparatively narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In this study, we have shown that many 31 P-containing metabolites measured using in vivo 31 P MRS are correlated due to spectral overlap. Like in the case of short echo time proton MRS these correlations are influenced by linewidth and interactions with the background spectral baseline [ 23 , 24 ], especially in the downfield region. Compared with 3 Tesla, metabolite–metabolite correlations are significantly reduced at 7 Tesla, highlighting a previously underappreciated benefit of high magnetic field MRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have shown that many 31 P-containing metabolites measured using in vivo 31 P MRS are correlated due to spectral overlap. Like in the case of short echo time proton MRS these correlations are influenced by linewidth and interactions with the background spectral baseline [ 23 , 24 ], especially in the downfield region. Compared with 3 Tesla, metabolite–metabolite correlations are significantly reduced at 7 Tesla, highlighting a previously underappreciated benefit of high magnetic field MRS.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between two variables A and B can be distorted by their correlation with a potentially intervening variable C. The influence of variable C can be illustrated using partial correlations. Specifically, the partial correlation coefficient between A and B with the influence of C excluded (r AB|C ) is defined as follows [ 24 , 25 ]: where r AB , r AC, and r BC are Pearson’s correlation coefficients measured experimentally. In the case of correlating a 31 P-containing metabolite (A) with a clinical metric (B), the measured Pearson’s correlation coefficient r AB could be significantly influenced by another 31 P MRS signal (C) overlapping with the 31 P signal of interest (A).…”
Section: Discussionmentioning
confidence: 99%